2016
DOI: 10.1007/s00276-016-1665-2
|View full text |Cite
|
Sign up to set email alerts
|

New anatomo-radiological findings of the lateral pterygoid muscle

Abstract: We consider that the use of transparent-plastinated anatomical sections and its good correlation with MRI images (in axial and oblique-sagittal planes) led to an accurate identification of TMJ structures, especially in relation to the lateral pterygoid muscle, that is now described as a multipennate muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…If sections 1.5–4.0 mm thick are desired, the piece is frozen at a very low temperature (generally −80°C) and then cut. The individual sections are then plastinated (Fritsch, ; Cook, ; Sora et al, , , , , ; Zhang and Lee, ; Leaper et al, ; Nash et al, , ; Sora and Genser‐Strobl, ; Fritsch et al, ; Al‐Ali et al, ; Elnady and Sora, ; Chen et al, ; Wegmann et al, ; Arredondo et al, ; Liu et al, ; Konschake and Fritsch, ; Liang et al, , ; Bernal‐Mañas et al, ; Thorpe Lowis et al, ; Ottone et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…If sections 1.5–4.0 mm thick are desired, the piece is frozen at a very low temperature (generally −80°C) and then cut. The individual sections are then plastinated (Fritsch, ; Cook, ; Sora et al, , , , , ; Zhang and Lee, ; Leaper et al, ; Nash et al, , ; Sora and Genser‐Strobl, ; Fritsch et al, ; Al‐Ali et al, ; Elnady and Sora, ; Chen et al, ; Wegmann et al, ; Arredondo et al, ; Liu et al, ; Konschake and Fritsch, ; Liang et al, , ; Bernal‐Mañas et al, ; Thorpe Lowis et al, ; Ottone et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…With this diamond saw it is possible to obtain sections that include metal or ceramic implants to study the interface of these biomaterials.von Hagens et al () indicated that specimens should be frozen to be cut, adding that the saw guide must be cooled to 0°C. Different researchers cut the sections at different temperatures: Steinke (), −35°C; Porzionato et al (), −20°C; Sora and Cook (), −75°C; Macchi et al () and Ottone et al (), −20°C; Scali et al (, ), −85°C; Bernal‐Mañas et al (), −20°C and −80°C. Different materials can be used to make the block in which the samples to be cut are frozen; Soal et al () described the use of polyurethane foam.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations